Acute Kidney Injury and Anemia in Infants with Primary Hyperoxaluria: Two Case Reports - Fallahzadeh, Mohammad Amin; Vahhab, Elham; Shirazi Yeganeh, Babak; Fallahzadeh, Mohammad Hossein (Journal of Pediatric Nephrology, 2019)
Primary hyperoxaluria is a rare hereditary disease that usually presents with renal stone, nephrocalcinosis and renal insufficiency. Anemia is usually expected secondary to chronic kidney disease or bone marrow oxalosis following hyperoxalemia. However, sudden onset of renal insufficiency and anemia is very unusual and not easily explained. In this report, we present two infants with histopathologic diagnosis of hyperoxaluria who presented with sudden onset of anuria and severe anemia that required blood transfusion. Both patients had normal body growth indices. Kidneys and urinary bladder x-rays in both infants and serial ultrasound evaluations in one of them did not reveal any renal stone or nephrocalcinosis. The other patient had multiple microcalculi in both kidneys on ultrasound. We may conclude that in any infant with unexplained acute kidney injury and anemia, hyperoxaluria must be considered and kidney biopsy can be conclusive. Keywords: Primary hyperoxaluria; Anemia; Infant; Acute kidney injury; Renal insufficiency.